Peripheral Nerve Blocks Are Associated With Decreased Early Medical Complications, Dislocations, and Opioid Consumption Following Total Hip Arthroplasty - Brian P. McCormick, MD; Sean B. Sequeira, MD; Mark D. Hasenauer, MD; Robert P. McKinstry, MD; Frank R. Ebert, MD; Henry R. Boucher, MD (Arthroplasty Today)
Background: Peripheral nerve blocks (PNBs) may be utilized for postoperative pain control following total hip arthroplasty (THA). The purpose of this study was to evaluate the association between PNBs and postoperative complication rates, healthcare utilization, and opioid consumption following elective THA. Methods: Opioid-naive patients who received PNBs on the same day as undergoing THA for degenerative etiologies were identified from a large national database and matched 1:5 to a control cohort using propensity scoring. Rates of medical complications, inpatient readmissions, and emergency department presentations occurring within 90 days of THA and surgery-related complications occurring within 1 year of THA were compared using odds ratios. Total cost and perioperative opioid consumption in morphine milligram equivalents (MMEs) per day were also evaluated and compared between groups. Results: Propensity score matching resulted in 4748 PNB patients matched to 23,740 control patients. THA patients who received PNBs had lower incidences of deep vein thrombosis (odds ratio [OR] 0.67, P = .004), urinary tract infection (OR 0.76, P < .001), and dislocation (OR 0.51, P < .001). PNBs were also associated with decreased perioperative opioid consumption (38.6 MME/day vs 55.3 MME/day, P < .001). Regarding healthcare utilization, there were no differences between cohorts in rates of inpatient readmission, emergency department presentation, or total cost. Conclusions: PNBs are associated with decreased risk of deep vein thrombosis, urinary tract infection, and dislocation and decreased perioperative opioid consumption following THA. Level of evidence: III, Retrospective review.